Ginkgo biloba: a natural reducing agent for the synthesis of cytocompatible graphene - Gurunathan S (Dove Medical Press, 2014)
Sangiliyandi Gurunathan, Jae Woong Han, Jung Hyun Park, Vasuki Eppakayala, Jin-Hoi Kim Department of Animal Biotechnology, Konkuk University, Seoul, South Korea Background: Graphene is a novel two-dimensional planar nanocomposite material consisting of rings of carbon atoms with a hexagonal lattice structure. Graphene exhibits unique physical, chemical, mechanical, electrical, elasticity, and cytocompatible properties that lead to many potential biomedical applications. Nevertheless, the water-insoluble property of graphene restricts its application in various aspects of biomedical fields. Therefore, the objective of this work was to find a novel biological approach for an efficient method to synthesize water-soluble and cytocompatible graphene using Ginkgo biloba extract (GbE) as a reducing and stabilizing agent. In addition, we investigated the biocompatibility effects of graphene in MDA-MB-231 human breast cancer cells. Materials and methods: Synthesized graphene oxide (GO) and GbE-reduced GO (Gb-rGO) were characterized using various sequences of techniques: ultraviolet-visible (UV-vis) spectroscopy, Fourier-transform infrared spectroscopy (FTIR), dynamic light scattering (DLS), scanning electron microscopy (SEM), atomic force microscopy (AFM), and Raman spectroscopy. Biocompatibility of GO and Gb-rGO was assessed in human breast cancer cells using a series of assays, including cell viability, apoptosis, and alkaline phosphatase (ALP) activity. Results: The successful synthesis of graphene was confirmed by UV-vis spectroscopy and FTIR. DLS analysis was performed to determine the average size of GO and Gb-rGO. X-ray diffraction studies confirmed the crystalline nature of graphene. SEM was used to investigate the surface morphologies of GO and Gb-rGO. AFM was employed to investigate the morphologies of prepared graphene and the height profile of GO and Gb-rGO. The formation of defects in Gb-rGO was confirmed by Raman spectroscopy. The biocompatibility of the prepared GO and Gb-rGO was investigated using a water-soluble tetrazolium 8 assay on human breast cancer cells. GO exhibited a dose-dependent toxicity, whereas Gb-rGO-treated cells showed significant biocompatibility and increased ALP activity compared to GO. Conclusion: In this work, a nontoxic natural reducing agent of GbE was used to prepare soluble graphene. The as-prepared Gb-rGO showed significant biocompatibility with human cancer cells. This simple, cost-effective, and green procedure offers an alternative route for large-scale production of rGO, and could be used for various biomedical applications, such as tissue engineering, drug delivery, biosensing, and molecular imaging. Keywords: alkaline phosphatase activity, atomic force microscopy, biocompatibility, cell viability, graphene, Fourier-transform infrared spectroscopy, scanning electron microscopy, Raman spectroscopy, UV-visible spectroscopy